BIOLOGICALLY INSPIRED PROTOCOL FOR SECURING A CLASS OF NETWORKS - MOHAMED, YASIR ABDELGADIR (2010)
Although a lot of efforts have been made and a lot of studies have been carried out in networking security, we cannot go so far as to say the security requirements for the different types of networks are satisfied. As applications that are applicable to different networks mature, new security methods are considered necessary. Infrastructure-less environments are dynamic and mostly difficult to control; hence security methods designed for other types of networks might not be applicable. Mobile Ad hoc Networks are subjected to more vulnerabilities than the fixed networks as they are self-organized, self-configured, and self-controlled infrastructure-less networks. As such, in this research we are concentrating more on securing mobile ad hoc networks. Within the wireless domain, packets are forwarded to the destination usually through the intermediate nodes that act as routers. Packets are more prone to different vulnerabilities while routed from a source to a destination passing through untrustworthy intermediate nodes. A change in one bit within an incoming packet may lead to serious security preaches.